Genomics and Virulence of Fonsecaea pugnacius, Agent of Disseminated Chromoblastomycosis - Bombassaro, Amanda; Schneider, Gabriela X.; Costa, Flávia F.; Leão, Aniele C. R.; Soley, Bruna S.; Medeiros, Fernanda; da Silva, Nickolas M.; Lima, Bruna J. F. S.; Castro, Raffael J. A.; Bocca, Anamélia L.; Baura, Valter A.; Balsanelli, Eduardo; et al. (Frontiers in Genetics, 2020)
Among agents of chromoblastomycosis, Fonsecaea pugnacius presents a unique type of infection because of its secondary neurotropic dissemination from a chronic cutaneous case in an immunocompetent patient. Neurotropism occurs with remarkable frequency in the fungal family Herpotrichiellaceae, possibly associated with the ability of some species to metabolize aromatic hydrocarbons. In an attempt to understand this new disease pattern, were conducted genomic analysis of Fonsecaea pugnacius (CBS 139214) performed with de novo assembly, gene prediction, annotation and mitochondrial genome assembly, supplemented with animal infection models performed with Tenebrio molitor in Mus musculus lineages BALB/c and C57BL/6. The genome draft of 34.8 Mb was assembled with a total of 12,217 protein-coding genes. Several proteins, enzymes and metabolic pathways related to extremotolerance and virulence were recognized. The enzyme profiles of black fungi involved in chromoblastomycosis and brain infection were analyzed with the Carbohydrate-Active Enzymes (CAZY) and peptidases database (MEROPS). The capacity of the fungus to survive inside Tenebrio molitor animal model was confirmed by histopathological analysis and by presence of melanin and hyphae in host tissue. Although F. pugnacius was isolated from brain in a murine model following intraperitoneal infection, cytokine levels were not statistically significant, indicating a profile of an opportunistic agent. A dual ecological ability can be concluded from presence of metabolic pathways for nutrient scavenging and extremotolerance, combined with a capacity to infect human hosts.